2019
DOI: 10.3389/fmicb.2019.02230
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Genetic Transformation System and Implications of the Type IV Restriction System in the Nitrogen-Fixing Plant Endosymbiont Frankia alni ACN14a

Abstract: Genus Frankia is comprised primarily of nitrogen-fixing actinobacteria that form root nodule symbioses with a group of hosts known as the actinorhizal plants. These plants are evolutionarily closely related to the legumes that are nodulated by the rhizobia. Both host groups utilize homologs of nodulation genes for root-nodule symbiosis, derived from common plant ancestors. The corresponding endosymbionts, Frankia and the rhizobia, however, are distantly related groups of bacteria, leading to questions about th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 77 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The unicellular paraphyletic rhizobia and filamentous Frankia sp. are phylogenetically separated, implying that the two main species of N 2 -fixing symbiotic bacteria have inherited N 2 -fixing mechanism through divergent evolutionary origins [201]. The expected benefit of the relationship for the host plants in all of these associations and symbioses is the fixed-nitrogen from the symbiotic partner, who will in return obtain reduced carbon and essential resources from the host plants [194,202].…”
Section: Leguminous and Non-leguminous Plantmentioning
confidence: 99%
“…The unicellular paraphyletic rhizobia and filamentous Frankia sp. are phylogenetically separated, implying that the two main species of N 2 -fixing symbiotic bacteria have inherited N 2 -fixing mechanism through divergent evolutionary origins [201]. The expected benefit of the relationship for the host plants in all of these associations and symbioses is the fixed-nitrogen from the symbiotic partner, who will in return obtain reduced carbon and essential resources from the host plants [194,202].…”
Section: Leguminous and Non-leguminous Plantmentioning
confidence: 99%
“…Also, the signaling molecules of Frankia are not similar to rhizobial NFs (lipo-chitooligosaccharides [LCOs]) [126]. The role of flavonoids for initial crosstalks between specific Frankia and actinorhizal host, leucine-rich repeat-type Symbiosis Receptor Kinase (SYMRK), calmodulin-dependent kinase (CaMK), calcium oscillation and calcium spiking, and the Nodule Inception (NIN) as signaling mechanisms have been foreseen in the literature [32,[127][128][129][130][131][132][133][134][135][136][137][138][139][140]. It has been revealed that the regulation of nodule organogenesis is a highly conserved phenomenon with several shared key components, namely, CCK and SYMRK, and so on in the common signaling pathway and infection process among all the members of nitrogen-fixing clade Rosid I and arbuscular mycorrhizal (AM) symbiosis [28,130,134,135].…”
Section: Cell Signalling and Functional Genomics Of Actinomycetes-pla...mentioning
confidence: 99%
“…ArI3 was grown in basal medium with propionate (BAP) ( 9 ) supplemented with 5 mM pyruvate and 5 mM morpholinepropanesulfonic acid (MOPS), as in reference 10 . Hyphae were collected using a 14G syringe needle, centrifuged at 10,000 rpm for 5 min, resuspended, and homogenized by passage through a 21G needle.…”
Section: Announcementmentioning
confidence: 99%
“…Genomic DNA (gDNA) was extracted using the cetyltrimethylammonium bromide (CTAB) protocol in reference 10 , purified by phenol-chloroform extraction, and stored in TE buffer at −20°C. The DNA was quantified using the Qubit 3.0 fluorometer with the double-stranded DNA (dsDNA) broad-range (BR) assay kit, cleaned and concentrated by mixing with 0.45× volume AMPure beads (Beckman Coulter Life Sciences) according to the manufacturer’s instructions, and used for library preparation according to the ONT 1D gDNA protocol (SQK-LSK109).…”
Section: Announcementmentioning
confidence: 99%